1992
DOI: 10.3109/09513599209081006
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss and menstrual cycle: clinical and endocrinological evaluation

Abstract: This study explores the clinical and endocrine implications of weight loss. The frequency of menstrual abnormalities was found to be greatly influenced by reduction in body weight. The occurrence of amenorrhea appeared to be proportional to the rate of weight loss, while regular cycles and luteal phase deficiency were inversely correlated to weight loss. Endocrine variations were noted. Significant decreases in luteinizing hormone and follicle stimulating hormone levels occurred only in amenorrheic patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Among women with weight loss, those in the highest tertile of PBB exposure experienced longer bleed length than women in the lowest tertile. Among the women in the lowest PBB tertile with weight loss, we observed shorter bleed length, as might be expected among women with weight loss in the general population [48-51]. We did not observe any differences in cycle length with PBB exposure or weight loss when PBB was categorized in tertiles.…”
Section: Discussionsupporting
confidence: 76%
“…Among women with weight loss, those in the highest tertile of PBB exposure experienced longer bleed length than women in the lowest tertile. Among the women in the lowest PBB tertile with weight loss, we observed shorter bleed length, as might be expected among women with weight loss in the general population [48-51]. We did not observe any differences in cycle length with PBB exposure or weight loss when PBB was categorized in tertiles.…”
Section: Discussionsupporting
confidence: 76%
“…The amenorrhea is considered to be caused by hypothalamic dysfunction; the pituitary-ovary axis is intact (Frisch, 1990). However, significant decreases in LH, FSH, and estradiol levels can occur in amenorrheic patients with a weight loss higher than 20% (Falsetti et al, 1992). The similar patterns of hormone changes found in our study suggested that weight loss might be a critical cause of the MA-related irregular menstruation.…”
Section: The Causes Of Hormone Deregulation May Be Multi-facetedsupporting
confidence: 69%
“…Thus menstrual problems, such as dysmenorrhea and amenorrhea were not differentiated, possibly obscuring relationships for particular subgroups. Amenorrhea has been shown to be associated with underweight 38 and one recent study that recorded details of duration and severity of menstrual pain in a twelve-month diary found increased risks for overweight women. 39 This speci®c ®nding relating to menstrual pain supports observations from the present study for nonspeci®c menstrual problems.…”
Section: Discussionmentioning
confidence: 99%